Pengaruh penambahan daun pandan terhadap mutu sirup nira aren - Herdianto Lantemona; Poen Tenggengan; Jongker Baali (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2022)
One of the industrial-based uses of palm trees is the manufacture of palm sap syrup. This study aims to determine the effect of pandan leaves on the quality of palm sap syrup in terms of color, taste and smell. The research was carried out at the Minaesa Institute of Technology campus laboratory in Tomohon City. In this study, the population was 5 bottles of palm sap syrup using pandan leaf treatment consisting of 0 g control variables and independent variables (30 g, 40 g, 50 g, and 60 g). The generated data is processed by using statistical analysis of Completely Randomized Design. The results showed that the treatment of pandan leaves addition to palm sap syrup with an average sugar content of 60% which was stored for 45 days obtained the value from the organoleptic test (sensory analysis of 2.85 to 3.4 (from ‘moderately like’ category to ‘like’ category). This study concluded that the addition of 30 g of pandan leaves is preferred by the panelists with a value of 3.0 to 3.7 for color, taste and smell (from ‘moderately like’ category to ‘like’ category).